Enhanching User Experience in E-Commerce Website Design Through the User Centered Design Approach: A Case Study - Hamidatun Nisa; Dr. Tenia Wahyuningrum; Khoem Sambath (Journal of Innovation Information Technology and Application (JINITA), 2025)
Many small-scale businesses in Indonesia rely on manual customer interaction workflows, leading to delays, inefficiencies, and missed opportunities in digital transactions. This study proposes designing and implementing a user-centered e-commerce website to streamline order processing, improve user autonomy, and reduce the operational burden on the business owner. Addressing management issues in small businesses requires creating a website that meets user needs. The User-Centered Design (UCD) methodology includes iterative stages of user research, requirements specification, interface design, and usability evaluation. A high-fidelity prototype was tested by 65 participants, resulting in 56 valid responses after data cleaning. Usability was evaluated through ISO/IEC 25022-based metrics, achieving a 67.86% completion rate, an average task time of 91.66 seconds, and an overall relative efficiency of 66.96%. Using the User Experience Questionnaire (UEQ), we measured user satisfaction, with five out of six dimensions rated as “Excellent”. The final system was implemented using Laravel and Filament, integrated with Midtrans for payment automation, Mailtrap for email testing, and a management dashboard for order tracking and status updates. This study demonstrates the practical application of UCD in the digital transformation of SMEs by delivering a fully functional, user-validated interface that enhances transactional clarity and customer experience. Compared to prior methods, the approach enables self-service ordering with reduced reliance on real-time manual responses. The findings offer a replicable reference for similar businesses seeking to implement user-focused digital solutions efficiently.